Antifungal activity In vitro of nanoemulsion prepared from neem oil (Azadirachta indica) - Hernández-Becerra, Josafat Alberto; Sánchez-Cerino, Ana Lidia; García-Galindo, Hugo Sergio; Torres-Palacios, Cristóbal; Ochoa Flores, Angélica Alejandra (Ecosistemas y Recursos Agropecuarios, 2023)
Nanoemulsions are an effective alternative in the protection, transport,and release of bioactive compounds, favoring greater solubility, stability, bioavailability,and efficacy. Neem oil contains compounds with a broad spectrum of biological activity,including antifungal capacity. Molds are responsible for the deterioration of many fruits, soextracts from plants represent ecologically viable postharvest handling alternatives. The aimof this work was to develop stable nanoemulsions with neem oil, evaluating its antifungalactivity against Aspergillus niger isolated from papaya fruits. Nanoemulsions with differentHydrophilic Lipophilic Balance (HLB) values were prepared using neem oil, deionized water,and non-ionic emulsifiers. The globule size, polydispersity index (PDI), and surface chargewas analyzed. The antifungal activity was evaluated through the poisoned food technique.Response surface methodology was used to identify an optimal formulation which consistedof 8.21% of neem oil, 1:3.28 oil:emulsifier ratio, and 16.2 of HLB. This nanoemulsionreached a globule size of 60 nm and was stable for 365 days. Nanoemulsions preparedwith commercial or freshly extracted neem oil were effective in inhibiting In vitro the growthof Aspergillus niger. This contrasted with trials where non-nano-emulsified oil was used.The use of nanoemulsions with neem oil represents a promising alternative in the control ofpostharvest deterioration caused by Aspergillus niger in fruits.
Keywords: Nanoemulsion; neem; antifungal activity; Azadirachta indica; Aspergillus niger